Is internet hampering mental health of medical students: a cross sectional study - Shinde, Rupesh D.; Rajderkar, Shekhar S. (International Journal Of Community Medicine And Public Health, 2018)
Background: Internet addiction was first studied in 1996 and findings were presented to American Psychological Association. Recent studies examined the prevalence of Internet addiction and investigated its causes. Internet users in India are around 205 million. Internet usage among medical students is high. Internet addiction has both physical and psychological withdrawal symptoms. This study aims to understand the patterns of internet use and its effects on mental health among medical college students. The objectives of the study were to study the patterns of internet usage among medical college students and to study the depression in them and its relation to internet usage. Methods: Cross sectional study was conducted in government medical college. Taking prevalence of mild internet addiction 34% from previous Indian studies, minimum sample size of 90 was calculated. 23 students of 1st, 2nd 3rd year and internship were randomly chosen for study. Pretested Young’s 20-item IAT scale and DASS 21 questionnaire was used for the study. Statistical analysis was done using percentage and chi square test. Results: Mild internet addiction was found in one third of medical students. Depression is seen in 61% of students with internet addiction. Conclusions: Internet addiction is affecting mental health of medical students.